Dampak Game Mobile Legends Terhadap Motivasi Belajar Remaja Di Desa Curug - Andreas Gabril Ericsen; Enjang Suherman (CV. ITTC INDONESIA, 2024)
The aim of this research is to find out how the learning motivation of teenagers in Curug Village is related to how intensely they play the Mobile Legends game. The popular online game that requires strategy and cooperation is called Mobile Legends. To obtain research data, a qualitative approach was used, such as observation and interviews. The research results show that the intensity of playing Mobile Legends influences teenagers' learning motivation, with varying impacts depending on the duration and frequency of playing. Adolescents who play for a long time tend to experience a decrease in learning motivation, while those who play for a limited duration do not show a significant decrease in learning motivation. The findings of this research can be a guide for parents, teachers, and legislators in managing teenagers' gaming habits to reduce the negative impacts and increase the positive impacts on their academic performance.